Peramalan Ekspor Migas di Indonesia Menggunakan Pendekatan Seasonal Autoregressive Integrated Moving Average with Exogenous (SARIMAX) - Nurhasanah, Eka; Sukmawaty, Yuana; Maisarah, Maisarah (Indonesian Journal of Applied Statistics, 2024)
Based on Republic of Indonesia Law No. 22 of 2001, oil and natural gas are vital commodities that play an important role in the country's economy. However, the export of Indonesian oil and gas has been fluctuating, making it necessary to have a strategic plan to prevent minimal exports in the future. This planning can be initiated by first gathering the necessary information. The aim of this research is to forecast oil and gas exports in Indonesia using the best possible model. The data used include the value and volume of Indonesian oil and gas exports. The method begins with determining the ARIMA model, followed by incorporating seasonal elements. ARIMA and SARIMA modeling will tentatively include exogenous variables. Subsequently, parameter estimation, significance tests, diagnostic tests, and the determination of the best model are performed. The research findings indicate that the best model is SARIMAX (1,1,0)(0,1,1)12. The forecast results show that the value of Indonesia's oil and gas exports will continue to increase until July 2024, followed by a and slow down after that. It is hoped that the government can prepare sufficient supply for export to prevent a deficit during that period.